Anthropocene poetics deep time, sacrifice zones, and extinction - Farrier, David 1979- (University of Minnesota Press, 2019)
"Anthropocene Poetics looks at contemporary anglophone poetry from Anthropocene, Plantationocene, and Multispecies perspectives, and sets out a poetics for thinking about 'geologic intimacy,' the deeply relational reality of 'sacrifice zones,' and processes of kin-making in a time of extinction"--
Keywords: Geschichte 1990-2015; Ökologie -- Motiv; Lyrik; Umwelt -- Motiv; Englisch; Ecology in literature; Plants in literature; English poetry / History and criticism; English poetry; Criticism, interpretation, etc